Aerobic Versus Resistance Exercise for Overweight: Is there a Difference in Reporting Quality? - Rohwer, Jonas; Weisser, Burkhard; Wegner, Manfred; Bünzen, Claudia (Sports Medicine International Open, 2025)
In the management of overweight, the implementation of exercise helps to create a caloric deficit and to lose weight. Several studies have shown poor reporting quality of exercise interventions for other diseases. Thus, the purpose of this study was to assess the completeness of exercise intervention reporting in randomized controlled trials (RCTs) for the treatment of overweight and to evaluate potential differences between exercise modalities. Two independent reviewers applied two intervention reporting guidelines to 47 RCTs on the management of overweight. The completeness of intervention reporting was evaluated using descriptive statistics. Potential differences in reporting quality between studies using aerobic exercise (AE) vs. studies using combined aerobic and resistance exercise (ARE) were calculated with a χ2 test. Overall, studies completed 61% and 47%, respectively, of the guideline items. The χ2 analysis of exercise modalities showed a significant difference for two items regarding exercise progression (91% AE vs. 38% ARE, p<0.001) and detailed description of exercises (0% AE vs. 50% ARE, p<0.001). Reporting of exercise interventions in the treatment of overweight was found insufficient. The detected differences between exercise modalities imply the need for improved guidelines.
Keywords: TIDieR; CERT; exercise interventions; reporting quality; overweight